Defensive Mechanisms For iOS And Android Devices Security Threats, Vulnerabilities, And Attacks - Mr. Inderjit Singh , Dr. Umesh Sehgal , Ms. Tanu Chopra (International Journal of Advanced Science and Technology, 2020)
There is no doubt that mobile phones play an essential part in human beings' life. Mobiles devices such as Android and iOS not only fulfil the need for personal life but also useful in business growth. In this era, smartphones sale is increasing day by day because mobile manufacturer companies are launching mobiles with the best hardware configuration to meet the requirements of end-users, and also many Internet Service Provider (ISP) companies provide the best service to mobile users around the globe. At the same time, the number of mobile security threats and challenges have been increased for both manufacturer companies and mobile users. In this paper, we provide different security threats, attacks, challenges, and vulnerabilities faced by several iOS and Android mobile devices and give solution to solve these problems. Also, we discuss basic defensive mechanisms, and advanced defensive mechanism approaches based on Deep Learning, and Bio Inspired to secure our business and personal details in mobile devices.